Serum Ischemia Modified Albumin Levels in Infertile Couples Underwent in Vitro Fertilization - Fatma Beyazıt; Osman Balcı; Magdi Adam; Hasan İnal; Yeşim Bardakcı; Nafiye Yılmaz (Medical Network, 2016)
OBJECTIVE: Ischemia-modified albumin (IMA) is a novel biomarker for diagnosis of distinct disease states including infectious diseases, coronary atherosclerotic disease, hypoxic fetal distress and diabetes mellitus. In vitro fertilization (IVF) is a medical process by which an egg is fertilized by sperm outside the body with varible success rates. It is important for the clinician to assess which women will get pregnant after IVF procedure. In this context we aimed to analyse the possible role of IMA in infertile couples underwent IVF. STUDY DESINGN: The study group comprised 30 patients with IVF failure, 27 patients with a successful IVF cycle and 34 fertile controls. IVF failure is defined as IVF that does not result in a pregnancy. A rapid, spectrophotometric Albumin Cobalt Binding (ACB) test was used to determine serum IMA levels and results were presented by absorbance units (ABSU). RESULTS: Serum IMA levels were 0.27 (0.07-0.58), 0.35(0.08-0.88), and 0.37(0.06-1.07) ABSU for patients with IVF cycle failure, successful IVF cycle and controls respectively. No statistically significant difference was observed between study participants. CONCLUSION: Our results showed that ischemia modified albumin did not provide enough sensitivity or specificity to determine IVF success.